CHANGES IN THE STATE OF THE BODY'S REGULATORY SYSTEMS IN A HEALTHY ADULT UNDER THE INFLUENCE OF SPELEOCLIMATOTHERAPY (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
Changes in the state of the body's regulatory systems by the parameters of cutaneous conductivity and heart rate variability in a healthy adult under the influence of speleoclimatotherapy have been studied. The study involved 29 2nd year students of VSMU named after V.I. N.N. Burdenko, Voronezh (21 girls and 8 boys, age 18-21). The course of speleoclimatotherapy included 10 sessions lasting 1 hour at a temperature of 18 ° C. All study participants gave written informed consent to participate in the study. Before the start of speleoclimatotherapy, on the 3rd, on the 10th day of speleoclimatotherapy and 7 days after the end of the course, we registered the skin conductivity (SCRS) and cardiac rhythm (HR) of patients with the help of PMO Analysis of signals via polygraphic channels combined with EEG signals «Encephalan -СА». It was revealed that the change in the activity of the body's regulatory systems in terms of the parameters of cutaneous conductivity and heart rate variability in an adult healthy person under the influence of speleoclimatotherapy depends on the sex of the subjects. In girls and boys, different mechanisms of the response of the regulatory systems of the body to the action of air ions are observed. At the same time, in both boys and girls, the central mechanisms of regulation do not participate in response to the speleoclimatic effect, the mechanism of action is determined by the work of internal physiological systems (intrasystem mechanisms) and the autonomic nervous system.
Keywords: speleocamera, speleoclimatotherapy, regulatory system, skin conduction, cardiac rhythm, tension.